Modern Culture and Factors Influencing Its Promotion - Tasbergenova, Gaukhar; Raimkulova, Aktoty; Begembetova, Galiya; Keshubayeva, Dinara; Sagiyev, Baurzhan (International Journal of Psychosocial Rehabilitation, 2020)
In the “value” interpretation, culture is understood as a combination of material and spiritual values of a people or humanity as a whole. Indeed, no society can exist and develop without accumulating the experience of previous generations, because only on their basis the life of subsequent ones becomes possible. Traditionally, culture is reduced to tradition, a system of norms, rules, patterns. However, especially in relation to modern, rapidly transforming culture, this approach is clearly insufficient. It is necessary to take into account new circumstances that effectively stimulate the formation and development of new cultures. In the first approximation, the three most obvious factors as the leading factors in modern cultural genesis are: urban lifestyle (metropolis), business activity (business and management as its technology), and the state (government). Misunderstanding of these factors can lead to and often leads to erroneous assessments of a number of modern processes, for example, globalization. The article examines the concept of “culture” multilaterally, and offers various scientific interpretations of it. The author defines the main factors affecting the promotion of culture. Each factor is consistently characterized.